Carboxymethylagarose-AuNPs generated through green route for selective detection of Hg2+ in aqueous medium with a blue shift. (6th March 2015) - Chaudhary, Jai Prakash; Kumar, Anshu; Paul, Parimal; Meena, Ramavatar
Highlights: Synthesis of biopolymer functionalized AuNPs employing a rapid and green route. Selective detection of Hg 2+ in aqueous media with a concomitant blue shift. Core etching fundamentals to detect Hg 2+ in form of Amalgam (Au–Hg). CMA-AuNPs exhibits efficiency to detects Hg 2+ in the range of 0.01–100 ppm. Gold metal was recovered from aqueous spent of solution using dil HNO3 . Abstract: We report here a facile, rapid, cost-effective method via a green route for the selective detection of Hg 2+ in aqueous media. In this study carboxymethylagarose (CMA) is used to generate gold nanoparticles and subsequently to act as a stabilizer for the CMA-functionalized gold nanoparticles (CMA-AuNPs). The resulting CMA-AuNPs was characterized by UV–visible, X-ray diffraction, transmission electron microscopy (TEM), dynamic light scattering (DLS), atomic force microscopy (AFM) and zeta potential measurements. Zeta potential value (∼ −73 mv) of CMA-AuNPs in the aqueous medium shows its higher stability. When CMA-AuNPs were exposed to an aqueous Hg 2+, a blue shift for its localized surface plasmon resonance absorbance (LSPR) band is observed along with significant colour change of the solution. The probe enables to detect Hg 2+ in the range of 0.01–100 ppm even in spiked lake water samples. This study offers a sustainable and eco-friendly route for selective detection of Hg 2+ in aqueous solution and may find potential application towards water purification.